The education gap : vouchers and urban schools - Howell, William G. (Brookings Institution Press, 2006)
The voucher debate has been both intense and ideologically polarizing, in good part because so little is known about how voucher programs operate in practice. In The Education Gap, William Howell and Paul Peterson report new findings drawn from the most comprehensive study on vouchers conducted to date. Added to the paperback edition of this groundbreaking volume are the authors' insights into the latest school choice developments in American education, including new voucher initiatives, charter school expansion, and public-school choice under No Child Left Behind. The authors review the significance of state and federal court decisions as well as recent scholarly debates over choice impacts on student performance. In addition, the authors present new findings on which parents choose private schools and the consequences the decision has for their children's education. Updated and expanded, The Education Gap remains an indispensable source of original research on school vouchers. "This is the most important book ever written on the subject of vouchers."--John E. Brandl, dean, Hubert H. Humphrey Institute of Public Affairs, University of Minnesota "The Education Gap will provide an important intellectual battleground for the debate over vouchers for years to come."--Alan B. Krueger, Princeton University "Must reading for anyone interested in the battle over vouchers in America."--John Witte, University of Wisconsin.
Keywords: Educational vouchers -- United States.; School choice -- United States.; Education, Urban -- United States.; Bons scolaires -- États-Unis.; Écoles -- Choix -- États-Unis.; Enseignement en milieu urbain -- États-Unis.; EDUCATION -- Finance.; EDUCATION -- Experimental Methods.; Education, Urban; Educational vouchers; School choice; United States